Sewage sludge compost in zoysia grass sod production - Mota, Flávia Diniz [UNESP]; Bôas, Roberto Lyra Villas [UNESP]; Mateus, Caroline de Moura D’Andréa [UNESP]; Silva, Tatiane Bortoletto Gomes da [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2019)
This study evaluated whether the use of composted sewage sludge in zoysia grass sod production can partially or completely substitute fertilization based on urea. The experiment was conducted on a sod farm located in Itapetininga, São Paulo State, Brazil. The experimental design was a complete randomized block design with five replications and experimental plots of 5 m 2 in a 2x6 factorial scheme. The first factor was the method of application (single or split), and the second factor was composted sewage sludge fertilization and two controls (no fertilization and a standard dose of conventional fertilizer). The conventional fertilizer (urea) dose corresponds to 300 kg N ha -1 and the sewage compost doses correspond to 100, 200, 300, and 400 kg N ha -1 . The experiment began with the liming of the total area at 60 days after the previous harvest of zoysia grass sod. Three methods were used to evaluate sod production: soil cover rate, green color intensity, and leaf analysis. At 212 days after the beginning of the experiment, the compost treatment of 30 Mg ha -1 (300 kg ha -1 of N), applied in a single dose, allowed for complete sod formation (100% soil cover rate).
Lodo de esgoto compostado na produção de grama esmeralda
Keywords: Nitrogen; Organic fertilization; Soil cover rate; SPAD; Turfgrass